1970
DOI: 10.3329/taj.v22i1.5029
|View full text |Cite
|
Sign up to set email alerts
|

The Changes in Levels of Serum Alanine Aminotransferase (ALT) During Anti Tubercular Treatment With 4FDC (Fixed Drug Combination)

Abstract: Tuberculosis (TB) is emerging as a major public health problem in Bangladesh, which now has the fifth highest burden of TB cases globally. Treatment of TB hampered with poor patient compliance and intolerance at least partly due to the adverse drug reactions, one of which is hepatotoxicity. Serum alanine aminotransferase level is an important indicator of such condition and impacts upon the continuation of anti tubercular treatment. A prospective randomized case study was conducted among 62 patients diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Among the full population 43 (39.09%) patients experienced at least one ADR during the time of study period ( Figure 1). The prevalence of ADR occurrence as per three different studies [5,10,11] during the intensive phase of ATT were found to be 22%, 30%, and 55%.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Among the full population 43 (39.09%) patients experienced at least one ADR during the time of study period ( Figure 1). The prevalence of ADR occurrence as per three different studies [5,10,11] during the intensive phase of ATT were found to be 22%, 30%, and 55%.…”
Section: Resultsmentioning
confidence: 86%
“…It is found that males were more prone to tuberculosis when compared to females with a ratio of 7:3. A study conducted by Mahmood et al [5], reveals that the pervasiveness of tuberculosis is more in males than females with a ratio of 5:1. Also the National Tuberculosis Program (NTP) summarized as the ratio of the occurrence of TB between the male and female were 5:2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation